Geochemistry of Dorojen volcanic rocks (SW Ardestan) with the special use of mineral chemistry of Propylitic alteration zones - mahboobeh jamshidibadr; Javad Moghadasi; Mohammadreza Ghorbani; Marzieh Sharifi; Mahnaz Salehi (پترولوژی, 2021)
Dorojin area in the Southwest of Ardestan city is part of the Urmia-Dokhtar magmatic zone. In the area of study, the intrusion of the Early Miocene granodiorite into the Middle-late Eocene sedimentary-volcanic complex caused the formation of hydrothermal propylitic alteration zones with green color. The vlcanics range in composition from basalt-andesite, trachyandesite, andesite, to rhyolite. These rocks under study are characterized by LREE and LILE enrichment compared to HFSE, calc-alkaline nature, and meta-aluminous composition related to the subduction zone. The most abundant mineral in the alteration zones is epidote formed by saussuritization of plagioclase. Average Pstacite [Fe3+/(Fe3++Al)×100] composition is 22% (PS22). Comb and radial textures are its remarkable textural features. Calcite is the second most abundant mineral in alteration zones. The nodules tourmaline is chemically dravite and alkaline. They have FeO/ (FeO+MgO)<0.6 and lower Al amount, high Mg, and low X site vacancy. Dravite composition and the Mg abundant reflect their alteration origin. Hence, they are regarded as hydrothermal tourmalines.  Titanite with CaO<25wt%, Al2O3<2wt% as well as Al2O3+TiO2 versus CaO, and Al/Fe on variation diagrams are indication of hydrothermal alteration. Ore mineral potential in the region points to the effect of hydrothermal fluids.